(untitled) (BIRDEM Medical Journal, 2019)
Background: Anemia is common in patients with chronic kidney disease (CKD) and this is generally anemia of chronic disease (ACD), but iron deficiency anemia (IDA) is also common. Soluble transferrin receptor (sTfR) is a useful marker for IDA. Present study was undertaken to assess the utility of sTfR as a marker of IDA and to differentiate ACD from IDA in selected group of Bangladeshi patients with CKD. Methods: This cross-sectional study was conducted in the Department of Nephrology, BSMMU, Dhaka, Bangladesh from January 2013 to December 2014. Patients with anemia admitted in Nephrology Department, whether on hemodialysis or not and Medicine Department of BSMMU were taken for study. The study population was further divided into two groups; Group A, patients (30) who were having IDA and Group B, patients (40) with ACD and a control group was also selected. Data were collected by face to face interview and laboratory investigations with a self-administered questionnaire. Results: The mean age of the patients in Group A and Group B were 38.40±13.23 and 34.85±10.52 years respectively and male-female ratio were 0.5:1 and 1:0.5. Mean sTfR level was higher (4.81± 1.64 μg/ml) in patients with IDA than (2.89±1.40 μg/ml) in patients with ACD (p <0.0001). Mean ferritin level was 599.59± 449.15μg/L in ACD patients whereas 101.23±119.42 in IDA patients (p<0.0001). Total iron binding capacity (TIBC) was more in ACD patients with sTfRe”3μg/ml as compared to ACD patients with sTfR<3μg/ml. Transferrin saturation (TSAT) level was significantly decreased in ACD patients with sTfRe”3μg/ml as compared to ACD patients with sTfR<3μg/ml. sTfR and ferritin indices between group A (IDA) and group B (ACD) shows mean sTfR:logSF level was significantly (P<0.001) high in group A (2.71±1.13) in comparison to group B (1.08±0.54). Mean log sTFR:SF was also significantly higher (P<0.05) in group A (0.001±0.0008) compared to group B (0.013±0.012). Conclusion: sTfR level has a comparable ability to serum ferritin in diagnosing IDA and ACD. However, sTfR and serum ferritin alone cannot definitely exclude coexisting iron deficiency in ACD. Log sTfR/ ferritin index has role in identifying development of iron deficiency in ACD whereas sTfR/ log SF ratio can differentiate pure IDA from ACD with or without iron deficiency. Thus, it is important to estimate both serum sTfR and sTfRferritin indices to be able to differentiate pure IDA, ACD and ACD with co-existing iron deficiency thus providing a non-invasive alternative to bone marrow iron. Birdem Med J 2019; 9(2): 151-156